Focus on grammar : workbook. A high-intermediate course for reference and practice - Fuchs,Marjorie. (Ngữ pháp Longman., 1997)
Present and past; Future; tag question, additions, and responses; gerund and infinitves; Passive; Modals;conditionals; adjective clauses...